2021
DOI: 10.1080/07448481.2021.1877142
|View full text |Cite
|
Sign up to set email alerts
|

Identifying vulnerable populations at a university during the COVID-19 pandemic

Abstract: Objective: Persons with high-risk for severe COVID-19 illness require special attention when considering university operations during the novel coronavirus pandemic. The objective of this study was to determine the number of students who fall within a high-risk category according to Centers for Disease Control and Prevention (CDC) guidelines using linked databases. Participants: Students enrolled at a large public University and who accessed the student health center between 2016 and 2020. Methods: Clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…This was problematic as particularly the decade before the pandemic, the mental health of students in US higher education was a growing issue as evidenced by the 2018 US National College Health Assessment which documented that 62.3% of respondents reported overwhelming anxiety and 41.4 reported beings so depressed they could not function anytime within the previous 12 months ( 31 ).The pandemic exacerbated these risks and increased the vulnerability of students to the psychological impact of COVID-19. However, studies indicate even if services are increased, student education and outreach about what services are available, and what mental health and mental health treatment entails, is needed to increase accessibility ( 32 , 33 ). This is particularly important as mental health issues are a primary obstacle to academic success ( 9 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This was problematic as particularly the decade before the pandemic, the mental health of students in US higher education was a growing issue as evidenced by the 2018 US National College Health Assessment which documented that 62.3% of respondents reported overwhelming anxiety and 41.4 reported beings so depressed they could not function anytime within the previous 12 months ( 31 ).The pandemic exacerbated these risks and increased the vulnerability of students to the psychological impact of COVID-19. However, studies indicate even if services are increased, student education and outreach about what services are available, and what mental health and mental health treatment entails, is needed to increase accessibility ( 32 , 33 ). This is particularly important as mental health issues are a primary obstacle to academic success ( 9 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Access and outreach of university mental health services is not only an ethical consideration but also a legal one. Tanabe et al ( 33 ) emphasize that case law recently determined that US universities have duty care which includes protecting students from foreseeable harm. Thus, continued advocacy for fully funded and policy-supported higher education institutional outreach and mental health services in various formats remains a priority ( 20 , 35 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The Philadelphia area boasts 80 secondary education institutes, many of which reside in the dense urban setting. Therefore, considerations extend beyond the vulnerable members of the university to those within the surrounding community [ 10 , 13 , 14 ]. An analytical modeling study found that an effective screening design, robust testing supplies, results management strategy, and compliance to mitigation efforts were crucial to successful university openings and keeping the community safe [ 13 ].…”
Section: The Third Phase: Expansionmentioning
confidence: 99%